Vascular disease and multiple sclerosis: a post-mortem study exploring their relationships - Geraldes, R; Esiri, MM; Perera, R; Yee, SA; Jenkins, D; Palace, J; DeLuca, GC (Oxford University Press, 2020)
Vascular comorbidities have a deleterious impact on multiple sclerosis clinical outcomes but it is unclear whether this is mediated by an excess of extracranial vascular disease (i.e. atherosclerosis) and/or of cerebral small vessel disease or worse multiple sclerosis pathology. To address these questions, a study using a unique post-mortem cohort wherein whole body autopsy reports and brain tissue were available for interrogation was established. Whole body autopsy reports were used to develop a global score of systemic vascular disease that included aorta and coronary artery atheroma, cardiac hypertensive disease, myocardial infarction and ischaemic stroke. The score was applied to 85 multiple sclerosis cases (46 females, age range 39 to 84 years, median 62.0 years) and 68 control cases. Post-mortem brain material from a subset of the multiple sclerosis (n = 42; age range 39–84 years, median 61.5 years) and control (n = 39) cases was selected for detailed neuropathological study. For each case, formalin-fixed paraffin-embedded tissue from the frontal and occipital white matter, basal ganglia and pons was used to obtain a global cerebral small vessel disease score that captured the presence and/or severity of arteriolosclerosis, periarteriolar space dilatation, haemosiderin leakage, microinfarcts, and microbleeds. The extent of multiple sclerosis-related pathology (focal demyelination and inflammation) was characterized in the multiple sclerosis cases. Regression models were used to investigate the influence of disease status on systemic vascular disease and cerebral small vessel disease scores and, in the multiple sclerosis group, the relationship between multiple sclerosis-related pathology and both vascular scores. We show that: (i) systemic cardiovascular burden, and specifically atherosclerosis, is lower and cerebral small vessel disease is higher in multiple sclerosis cases that die at younger ages compared with control subjects; (ii) the association between systemic vascular disease and cerebral small vessel disease is stronger in patients with multiple sclerosis compared with control subjects; and (iii) periarteriolar changes, including periarteriolar space dilatation, haemosiderin deposition and inflammation, are key features of multiple sclerosis pathology outside the classic demyelinating lesion. Our data argue against a common primary trigger for atherosclerosis and multiple sclerosis but suggest that an excess burden of cerebral small vessel disease in multiple sclerosis may explain the link between vascular comorbidity and accelerated irreversibility disability.